Surgical management of Gastro-duodenal Artery Pseudoaneurysm: A Case Report - Abdul Haseeb, Amina Arif, Sana Hamayun, Alvina Karam, Waseem Khan, Haq Nawaz (Pakistan Journal of Medical & Health Sciences, 2022)
Gastro duodenal artery (GDA) Pseudo aneurysm is a rare cause of Upper GIT bleeding. It can be fatal in case of a rupture and has a very high risk of Mortality. Advanced Diagnostic techniques like CT Angiography should be carried out earlier in the disease course for Prompt Diagnosis. Here we discuss a case of a successfully surgically treated GDA pseudo aneurysm Keywords: GDA Pseudo aneurysm; surgical resection; Embolization; Visceral artery Aneurysm